Segodnia v mire . Segodnia v mire . The World Today . Сегодня в мире - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Service tenure extended in the West German army; signing of the mid-range nuclear forces treaty; expansion of economic ties between Western European countries. Featured in the program: Kohl, Helmut (Chancellor of Germany); Jakeš, Miloš (General Secretary of the Czechoslovakian Communist Party); Varkoni, Petr (Hungarian Foreign Minister); Genscher, Hans-Dietrich (German Foreign Minister) Contributors: Zholkver, Aleksandr (Anchor) Series description: An information program of the Central Television of the USSR (CT USSR). The hosts were Igor Fesunenko, Valentin Zorin, Farid Seiful-Muliukov, and others. The program was first broadcasted on December 1, 1978 and was broadcasted until 1988. Продление срока службы в западной германской армии, договор о ликвидации ракет средней и меньшей дальности, расширение экономических связей между странами западной Европы. В программе участвуют: Коль, Гельмут (Федеральный канцлер Германии); Якиш, Милош (Генеральный секретарь Коммунистической партии Чехословакии); Варкони, Петр (Министр иностранных дел Beнгpии); Геншер, Ганс-Дитрих (Министр иностранных дел Германии) Создатели: Жолквер, Александр (Ведущий/Ведущая) Описание серии: Информационная телепередача Центрального телевидения СССР. Ведущие — Игорь Фесуненко, Валентин Зорин, Фарид Сейфуль-Мулюков и другие. Первый выпуск передачи вышел в эфир 1 декабря 1978 года. Выходила до 1988 года